Impact of medical school on quality of life and mental health in Brazil: a cross-sectional comparative study - Marina Silveira de Resende; Isabelle Martins Santos; Eduardo Cardoso de Moura; Renata de Almeida Pedro; Marcelo Gobbo (BMJ Open)
Objectives This study aimed to compare the perceptions of quality of life (QoL) and mental health among medical students and their peers in other university courses in Brazil through a cross-sectional analysis. We hypothesised that medical students face greater psychological challenges due to the demanding nature of their academic workload. Previous studies have indicated that medical training is associated with a decline in empathy and an increase in stress and anxiety, particularly during the clinical phase, when students face greater exposure to patient care and emotionally demanding experiences. These factors contribute to decreased psychological well-being, highlighting the need for targeted interventions in medical education. To address these challenges, this study investigates the specific impact of medical education on students’ mental health and QoL, aiming to identify potential structural changes that could mitigate these negative outcomes.Design A cross-sectional study was conducted in private higher education institutions in Brazil.Setting Data were collected online via the QuestionPro platform in August 2024, encompassing 32 units located across 14 states and 4 geographic regions in Brazil.Participants The sample included 10 844 students, 33.7% of whom were enrolled in medicine and 66.3% in other fields (administration, agronomy, agribusiness, systems analysis and development, architecture, architecture and urbanism, biomedicine, computer science, accounting, economics, social communication/advertising and propaganda, law, physical education, nursing, civil engineering, computer engineering, production engineering, electrical engineering, mechatronics engineering, aesthetics and cosmics, pharmacy, physics, physiotherapy, speech, speech therapy, environmental management, commercial management, human resources management, financial management, history, Portuguese-English literature, logistics, marketing, mathematics, veterinary medicine, nutrition, dentistry, pedagogy, management processes, psychology, advertising and propaganda, computer networks, social work, information systems and theology). The inclusion criterion was as follows: regularly enrolled students. The exclusion criteria were refusal to provide consent and incomplete questionnaires.The margin of error, calculated as 0.9 percentage points at a 95% CI, was based on a population of 74 684 students enrolled in the private institutions participating in the study.Primary and secondary outcomes Primary outcomes included QoL assessment via the WHOQOL-Brief Version and a customised questionnaire developed by the researchers. This questionnaire evaluated variables such as inclusion, accessibility, sports practices, adaptation and satisfaction with undergraduate training. Secondary outcomes assessed factors such as risky substance use, academic satisfaction and mental health conditions, including symptoms of anxiety and depression.Results Medical students exhibited significant declines in physical QoL (64.5–57.1, p<0.001) and psychological QoL (63.1–53.7, p<0.001) when students at the beginning of the course were compared with those near graduation. Additionally, symptoms of anxiety and depression were more prevalent among medical students, with 61.8% reporting current anxiety and 28.1% reporting current depression. The use of substances, including antidepressants and cognitive enhancers, such as ‘smart drugs’, was also greater among medical students than among their peers from other courses (21.4% and 11.2%, respectively). These findings underscore the urgency of implementing targeted mental health interventions and institutional reforms to increase the QoL of medical students.Conclusions This study reveals that medical students in Brazil experience a significant decline in QoL and mental health, particularly in the psychological and physical domains, as they progress through their academic journey. The higher prevalence of anxiety, depression and substance use among medical students than among peers in other fields underscores the intense emotional and academic pressures within medical education. These statistically significant findings highlight the critical need for comprehensive mental health support, curriculum adjustments to promote well-being and inclusive institutional policies. Implementing such measures is vital to enhance student welfare and foster resilient future healthcare professionals. Longitudinal research is necessary to assess the long-term impact of these interventions and to further explore systemic inequalities affecting student well-being.